GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 2138 species occurrences available in GBIF matching the query: TaxonKey: Richardia scabra L.. The dataset includes 2138 records from 126 constituent datasets: 4 records from OEH Atlas of NSW Wildlife. 1 records from HUEM - Herbário da Universidade Estadual de Maringá. 4 records from Phanerogamic Botanical Collections (S). 2 records from PRECIS (KwaZulu-Natal Herbarium). 1 records from University of Vienna, Institute for Botany - Herbarium WU. 1 records from UFG - Herbário da Universidade Federal de Goiás. 6 records from Census of the flora of Benin. 2 records from IAC - Herbário do Instituto Agronômico de Campinas. 77 records from Naturalis Biodiversity Center (NL) - Botany. 2 records from SPSF - Herbário Dom Bento José Pickel. 17 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 100 records from PRECIS. 2 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 3 records from UFP - Herbário UFP - Geraldo Mariz. 1 records from IICT Herbário LISC. 19 records from Herbario Universidad de Antioquia (HUA). 31 records from The digitization of plant specimens of NTU. 17 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 11 records from Herbier du Bénin. 10 records from MBM - Herbário do Museu Botânico Municipal. 1 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Herbario Museo de La Salle Bogotá (MLS). 1 records from Digital Florula - Las Cruces Biological Station. 105 records from Especímenes INBio. 20 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 53 records from Australia's Virtual Herbarium. 1 records from Natural History Museum Maastricht (NL) - Herbarium. 4 records from iNaturalist research-grade observations. 10 records from CONN. 2 records from University of Lethbridge Herbarium (LEA). 36 records from Louisiana State University Herbarium - Vascular Plants. 2 records from ALCB - Herbário Alexandre Leal Costa. 36 records from NMNH occurrence DwC-A. 1 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 1 records from OAC-BIO Herbarium. 2 records from naturgucker. 8 records from Flora Atlas N.T.. 35 records from ASE - Herbário da Universidade Federal de Sergipe. 1 records from UEC - Herbário da Universidade Estadual de Campinas. 3 records from FUEL - Herbário da Universidade Estadual de Londrina. 27 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 7 records from Herbario del CIBNOR. 1 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 3 records from Herbaria of the University and ETH Zürich. 522 records from Missouri Botanical Garden. 8 records from Natural History Museum (London) Collection Specimens. 2 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 2 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 2 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 1 records from Lista florística preliminar de Tamaulipas. 6 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 3 records from Composición florística del Parque Nacional Huatulco. 1 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 1 records from Plantas exóticas del centro de México y obtención de imágenes para una flora virtual de malezas. 4 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 1 records from Base de datos sobre la flora de Durango. 3 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 3 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 6 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 2 records from Australian National Herbarium (CANB). 19 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 1 records from The AAU Herbarium Database. 5 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 77 records from herbario. 1 records from Plant Specimens of Kurashiki Museum of Natural History. 2 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 15 records from Herbarium (UNA). 6 records from NSW herbarium collection. 2 records from Herbarium Berolinense. 1 records from Biologiezentrum Linz. 1 records from Institut Botanic de Barcelona, BC-Histórico. 16 records from Herbarium de Geo. B. Hinton, México. 2 records from Vascular Plants Collection of Sagamihara City Museum. 2 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from CVRD - Herbário da Reserva Natural Vale. 4 records from Árboles de la Península de Yucatán, Flora del Distrito de Tehuantepec, Oaxaca y Familia Asteraceae en México (IBUNAM). 17 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 2 records from Herbarium Specimen of the Institute of Traditional Medicine, Tanzania. 72 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from EKY_Darwincore. 27 records from MISS_DC_01MAR2006. 1 records from UA Herbarium. 9 records from R. L. McGregor Herbarium Vascular Plants Collection. 2 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 1 records from HUTO - Herbário da Universidade de Tocantins. 3 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 19 records from Database of Native Plants in Taiwan. 2 records from Herbier de la Guyane. 16 records from Herbarium of Taiwan Forestry Research Institute. 83 records from Precis Plant Data. 15 records from National vegetation diversity inventory and mapping plan. 1 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 3 records from HURB - Herbário do Recôncavo da Bahia. 1 records from HVAT - Herbário do Vale do Taquari. 2 records from Geographically tagged INSDC sequences. 4 records from HVASF - Herbário Vale do São Francisco. 4 records from HST - Herbário Sérgio Tavares. 161 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 8 records from Bernice P. Bishop Museum. 2 records from CRI - Herbário Pe. Dr. Raulino Reitz. 3 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 2 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 20 records from Colección del Herbario PSO de la Universidad de Nariño. 4 records from Royal Botanic Garden Edinburgh Herbarium (E). 6 records from Botany (UPS). 51 records from Instituto de Ciencias Naturales. 2 records from JPB - Herbário Lauro Pires Xavier. 4 records from EAC - Herbário Prisco Bezerra. 8 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 6 records from Herbario de la Universidad Industrial de Santander. 5 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 5 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 33 records from Institute of Ecology and Evolutionary Biology, National Taiwan University. 94 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 1 records from Digital Florula - Palo Verde Biological Station. 13 records from UB - Herbário da Universidade de Brasília. 2 records from Herbarium - Las Cruces Biological Station. 1 records from Allan Herbarium (CHR). 4 records from SysTax - Botanical Gardens. 2 records from HPL - Herbário do Jardim Botânico Plantarum. 4 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 2 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 4 records from Geneva Herbarium – General Collection (G). 7 records from Instituto de Botánica Darwinion. 1 records from UESC - Herbário Universidade Estadual de Santa Cruz.
Keywords: GBIF; biodiversity; species occurrences